Are Primary Funding Sources and Debt Level Associated with Career Outcomes Among Recent STEM Doctoral Graduates?. (29th July 2022) - Kim, Dongbin; Kim, Sehee; Flores, Amanda; Palek, Angela M.
ABSTRACT: This study examines how primary funding sources during doctoral program including loans, RAships, TAships, fellowships, and personal/family support, are associated with career outcomes among STEM doctoral graduates. Using the 2013 Survey of Earned Doctorates (SED) data commissioned by the NSF, we conducted a series of logistic and multinomial models and found that primary funding sources with different debt levels have distinct effects on career prospects among recent STEM doctoral graduates. Implications for theory, policy, and future research are discussed.